Effectiveness and safety of Linggui Zhugan decoction for the treatment of premature contraction in patients with coronary heart disease: A systematic review and meta-analysis - Liu, Longkun; Zhao, Yan; Birling, Yoann; Sun, Yuxin; Shang, Qinghua; Hu, Zhong-Jing; Liu, Jianping; Liu, Zhaolan (Frontiers in Cardiovascular Medicine, 2022)
Objective. To evaluate the effectiveness and safety of Linggui Zhugan decoction (LZD) as an adjunct treatment of cardiac arrhythmia in patients with coronary heart disease. Methods. PubMed, Embase, Web of Science, ClinicalTrials.gov, Cochrane Library, Chinese Knowledge Infrastructure, Wanfang database, Sino Med, VIP database were searched from inception until July 2022. Two reviewers selected independently randomized controlled trials testing the effect of LZD combined with conventional antiarrhythmic drugs on clinical effectiveness which was considered as primary outcome, times of premature junctional beats in 24 hours after treatment or adverse reactions in CHD patients with cardiac arrhythmia compared to conventional antiarrhythmic drugs only. The Cochrane risk of bias 2 tool was used for the Risk of bias assessment. Meta-analysis was conducted with Revman 5.4.1. and RStudio. Results. A total of 14 studies including 1236 participants were included. The primary outcome indicated that, compared with antiarrhythmic drugs alone (especially β Receptor blockers), the combination of LZD and conventional antiarrhythmic drugs resulted in higher clinical effectiveness [RR = 1.29, 95% CI: (1.22,1.36)] and lower number of premature junctional beats in 24 hours [MD = -71.14, 95% CI: (-76.23,-66.06)] at end-of-intervention. The differences in adverse reactions [RR = 0.42, 95%CI: (0.15,1.14), p = 0.09] were not significant. Risk of bias was marginally high among the studies. Funnel plot and Harbord’s test [t = 1.63, p = 0.1346] indicated no existence publication bias. Conclusion. The current evidence shows that LZD can increase the effectiveness of conventional antiarrhythmic drugs for cardiac arrhythmia in patients with coronary heart disease. However, the results should be interpreted with caution because of the high overall risk of bias. Future studies with appropriate randomization and double-blind methods are warranted to confirm these findings.